Upcycling unexplored dregs and biomass fly ash from the paper and pulp industry in the production of eco-friendly geopolymer mortars: A preliminary assessment. (30th September 2018) - Novais, Rui M.; Carvalheiras, J.; Senff, L.; Labrincha, J.A.
Graphical abstract: Highlights: Two unexplored waste streams from pulp and paper industry were investigated. Dregs were used for the first time as filler in geopolymeric mortars production. Biomass fly ash was used as main aluminosilicate source (75 wt%). Dregs enhanced mortars' tensile (up to 71%) and compressive strength (up to 34%). Using dregs as additives in geopolymers is an effective waste recycling strategy. Abstract: Green liquor dregs wastes coming from pulp and paper production are currently disposed in landfills at a huge cost for industry and the environment. In this work, a novel and more sustainable waste management strategy is proposed. Dregs were used for the first time as fine filler in the production of biomass fly ash-based geopolymeric mortars. The influence of the dregs incorporation amount on the fresh (geopolymer kinetics and mortars workability) and hardened-state (mechanical resistance, water absorption and capillary water absorption) properties of the mortars was evaluated. Although dregs incorporation reduce the flow workability (up to 19%), their presence and amount did not significantly alter the geopolymerization kinetics. Additionally dregs-containing mortars exhibited enhanced tensile (up to 71%) and compressive strength (up to 34%), and lower water absorption in comparison with the reference mortar. These results demonstrate the feasibility of using dregs as fine filler in geopolymers production. Moreover the mortars were produced using mainly biomass fly ash waste as aluminosilicate source which further reduces the environmental impact of the pulp and paper industry.